Demographic analysis for agroecology adoption in sugar palm agroindustry: evidence from Deli Serdang Regency - Farida Yani; Rahmat Syahni; Novizar Nazir; Tzong-Ru (Jiun-Shen) Lee; Rika Ampuh Hadiguna (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
This study explores the potential of agroecology in developing a sustainable sugar palm agroindustry in Deli Serdang Regency, North Sumatra, Indonesia. The sugar palm (Arenga pinnata) is a vital economic resource, yet its development faces limited technology, traditional management practices, and low-quality seed availability. The research aims to analyze the demographic characteristics influencing the adoption of agroecological principles among sugar palm craftsmen and assess the agroindustry's sustainability and productivity. A qualitative descriptive approach was employed, involving in-depth interviews with 100 respondents, including sugar palm farmers and craftsmen, alongside secondary data from the Central Statistics Agency. The findings reveal that most artisans are in the productive age group, with low formal education but significant practical experience. While 65% of respondents practice crop diversification, challenges remain in soil conservation and adopting environmentally friendly technologies. The study forecasts increased palm sugar production, projecting growth from 664.4 tons in 2022 to 790.8 tons by 2026, indicating potential for enhanced productivity. Integrating traditional knowledge with modern agroecological practices is essential for improving sustainability and competitiveness in the sugar palm agroindustry. Training programs that respect traditional values while promoting sustainable practices are necessary to empower artisans and enhance regional food security. This research underscores the importance of community collaboration among farmers, government, and research institutions to foster a more resilient and equitable agroecological system.